2018
DOI: 10.4103/njcp.njcp_343_17
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of allergic diseases among children with asthma: What is the impact on asthma control in South East Nigeria?

Abstract: Allergic diseases are common in children with asthma in our environment, but did not significantly impact on asthma control. Socioeconomic factors such as urbanization and family size had effects on the achievement of asthma control but not on allergy status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 1 publication
1
21
0
Order By: Relevance
“…In this study, majority (50.0%) of the study participants had well-controlled asthma. Studies reported by Ayuk et al [11] and Omole et al [12] had similar findings with this study. Kuti and Omole [13] reported a higher percentage of 83.7% of well-controlled asthma among Ilesa children.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, majority (50.0%) of the study participants had well-controlled asthma. Studies reported by Ayuk et al [11] and Omole et al [12] had similar findings with this study. Kuti and Omole [13] reported a higher percentage of 83.7% of well-controlled asthma among Ilesa children.…”
Section: Discussionsupporting
confidence: 92%
“…24 The most common concomitant atopic diseases are asthma (15% -64%), allergic rhinitis (30% -49%) and eczema (16% -24%). 19,20,25 In another earlier study, atopy was common in patients with palpebral or tarsal form of the disease compared with the limbal form. 26 Moreover, VKC is also associated with a family history of other inflammatory diseases such as psoriasis and thyroiditis.…”
Section: Epidemiologymentioning
confidence: 92%
“…Interestingly, this is usually attributed to consanguineous marriages. 25 This further emphasises the need for a detailed case history when examining patients with VKC in order to fully understand any possible associated causative factors of the disease.…”
Section: Other Factors Associated With Vernal Keratoconjunctivitismentioning
confidence: 99%
“…All three studies conducted in Nigeria, South Africa and Uganda [19][20][21] were cross-sectional; two hospital-based and one community-based. The sample size was smaller for hospital-based studies with 207 and 115 participants in Nigeria 19 and South Africa, 20 respectively, compared with the community-based study of 561 participants in Uganda. 21 Publication dates ranged from 2014 to 2019.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Interestingly, the children who lived in rural areas without concurrent allergy had poorly controlled asthma (50.0%) compared with their urban counterparts (28.3%), Fisher's exact test=2.076, p=0.17, although this too was not significant. 19 All three included studies considered the presence of asthma triggers in their participants' environments, but only the South African study examined these triggers in relation to asthma control. Common triggers included dust, cold air, physical exercise, fumes or air pollution, pollen, pets, smoking and biomass fuels (figure 2).…”
Section: Environmental Related Factorsmentioning
confidence: 99%